Contribution of IL-1RI Signaling to Protection against Cryptococcus neoformans 52D in a Mouse Model of Infection - Shourian, Mitra; Ralph, Ben; Angers, Isabelle; Sheppard, Donald C.; Qureshi, Salman T. (Frontiers in Immunology, 2018)
Interleukin-1 alpha (IL-1α) and interleukin-1 beta (IL-1β) are pro-inflammatory cytokines that are induced after Cryptococcus neoformans infection and activate the interleukin-1 receptor type I (IL-1RI). To establish the role of IL-1RI signaling in protection against cryptococcal infection, we analyzed wild-type (WT) and IL-1RI-deficient (IL-1RI−/−) mice on the BALB/c background. IL-1RI−/− mice had significantly reduced survival compared to WT mice after intratracheal challenge with C. neoformans 52D. Microbiological analysis showed a significant increase in the lung and brain fungal burden of IL-1RI−/− compared to WT mice beginning at weeks 1 and 4 postinfection, respectively. Histopathology showed that IL-1RI−/− mice exhibit greater airway epithelial mucus secretion and prominent eosinophilic crystals that were absent in WT mice. Susceptibility of IL-1RI−/− mice was associated with significant induction of a Th2-biased immune response characterized by pulmonary eosinophilia, M2 macrophage polarization, and recruitment of CD4+ IL-13+ T cells. Expression of pro-inflammatory [IL-1α, IL-1β, TNFα, and monocyte chemoattractant protein 1 (MCP-1)], Th1-associated (IFNγ), and Th17-associated (IL-17A) cytokines was significantly reduced in IL-1RI−/− lungs compared to WT. WT mice also had higher expression of KC/CXCL1 and sustained neutrophil recruitment to the lung; however, antibody-mediated depletion of these cells showed that they were dispensable for lung fungal clearance. In conclusion, our data indicate that IL-1RI signaling is required to activate a complex series of innate and adaptive immune responses that collectively enhance host defense and survival after C. neoformans 52D infection in BALB/c mice.